A coupled meshless-SBFEM-FEM approach in simulating soil-structure interaction with cross-scale model. Issue 136 (September 2020) - Gong, Jin; Zou, Degao; Kong, Xianjing; Liu, Jingmao; Chen, Kai
Abstract: This paper presents an integrated, customized routine that uses object-oriented programming and a "super element class" to apply an integrated approach to simulate soil-structure interaction (SSI) problems. The scaled boundary finite element method (SBFEM) and finite element method (FEM) are applied together with the quad tree technique to implement cross-scale modeling for solid elements. Meanwhile, the meshless interface seamlessly connects mismatched and differing sizes of meshes between the soil and the structure, thus allowing cross-scale modeling at the interface level. In addition, through modify the radial point interpolation function (RPIM) and the method of searching supporting nodes, the precision near the boundaries of meshless interface are improved, and circular (cambered) type interfaces can be simulated. Thus, through a coupled Meshless-SBFEM-FEM approach, a fine analysis of soil-structure interaction problem with multilevel cross-scale model can be conducted. Highlights: This paper presents a modified RPIM function and significantly improve the accuracy of interpolation near the boundary. The meshless interface is extended to simulate the interface with circular (cambered) types' interfaces. Through the object-oriented programming the meshless interfaces and SBFEM is integrated to FEM frameworks. The coupled Meshless-SBFEM-FEM can effectively achieve the multilevel cross-scale model in SSI problems. Several examples have confirmed the accuracy and flexibility of the proposed Meshless-SBFEM-FEM.